THERMODYNAMIC ANOMALIES AT THE PEIERLS TRANSITION IN BLUE BRONZE - CHUNG, M; KUO, YK; ZHAN, X; FIGUEROA, E; BRILL, JW; MOZURKEWICH, G (ELSEVIER SCIENCE SA, 1995)
Thermodynamic response functions have been measured on pieces of a single crystal of blue bronze at its 180K charge-density-wave (CDW) transition and are analyzed using a free energy appropriate for a 3D-XY model.
Keywords: CHARGE-DENSITY-WAVE; THERMAL-EXPANSION; PHASE-TRANSITION; HEAT